Identifikasi Sebaran Dan Volume Pasir Besi Menggunakan Metode Geolistrik Konfigurasi Wenner-Schulumberger Dan Analisis Kandungan Fe Didalamnya Menggunakan X-Ray Fluorescence Di Desa Paca Bagian Selatan - Papuling, Eminia Sofya; Sadjab, Bayu Achil; Kurnia, Kurnia; Buka, Oktosea; Janis, Harsen Berg; Yusniar, Masitah; Nur, Adrian Rahmat; Anwar, Haerul (Physikos: Journal of Physics and Physics Education, 2023)
This research uses the Naniura NRD300 HF tool to apply the Wenner-Schlumberger configuration geoelectric method which aims to determine the direction of distribution of iron sand, the volume of iron sand, and the Fe2O3 concentration of iron sand in the southern Paca beach area. The collected measurement results are then processed by RES2DINV software into a 2 Dimensional (2D) cross section which shows the distribution value of the subsurface layer as shown by a color image. After being saved in (.xyz) format, the RES2DINV software results are processed in RockWork software to create a pseudo-3D cross section. The RES2DINV software results show a resistivity value between 0,0761 – 3,59 Ωm which is identified as iron sand with a volume of 13,304 m3 at a depth of 2,50 – 9 meters from the surface of the datum point, while on track 2, the resistivity value ranges between 0,414 – 3,13 Ωm, and at a depth of 2,50 – 7 meters from the surface of the datum point with a volume reaching 12,883 m3 based on the results of the RockWork software. The distribution of iron sand deposits in the study area is from south to north. The method used to determine the composition of minerals present in a sample is called X-ray fluorescence (XRF). The results of the analysis of the Fe2O3 content in the first pass were 36,704% and in pass 2 it was 35,500%.